Studying antibiotic–membrane interactions via X‐ray diffraction and fluorescence microscopy. Issue 1 (15th June 2015) - Sun, Yi-Ting; Huang, Ping-Yuan; Lin, Cheng-Hao; Lee, Kuan-Rong; Lee, Ming-Tao
Abstract : Antibiotic drug resistance is a serious issue for the treatment of bacterial infection. Understanding the resistance to antibiotics is a key issue for developing new drugs. We used penicillin and sulbactam as model antibiotics to study their interaction with model membranes. Cholesterol was used to target the membrane for comparison with the well‐known insertion model. Lamellar X‐ray diffraction (LXD) was used to determine membrane thickness using successive drug‐to‐lipid molar ratios. The aspiration method for a single giant unilamellar vesicle (GUV) was used to monitor the kinetic binding process of antibiotic–membrane interactions in an aqueous solution. Both penicillin and sulbactam are found positioned outside the model membrane, while cholesterol inserts perpendicularly into the hydrophobic region of the membrane in aqueous solution. This result provides structural insights for understanding the antibiotic–membrane interaction and the mechanism of antibiotics. Abstract : We present antibiotic‐induced membrane thinning of a multi‐lamellar thin film sample. Both penicillin and sulbactam are found positioned outside the model membrane in an aqueous solution. We demonstrate a hybrid method to study the antibiotic–membrane interaction.